Optimizing protein and lipid levels in practical diet for juvenile northern snakehead fish (Channa argus) - Sagada, Gladstone; Chen, Jianming; Shen, Binqian; Huang, Aixia; Sun, Lihui; Jiang, Jianhu; Jin, Chunhua (Animal Nutrition, 2017)
A 3 × 3 factorial feeding trial was conducted to evaluate the production response of juvenile northern snakehead fish (Channa argus). Nine diets containing 3 protein levels (45%, 48% and 51%) and 3 lipid levels (9%, 12% and 15%) were formulated and fed to triplicate groups of juvenile northern snakehead (15.78 ± 0.09 g/fish) for 8 weeks. The formulated diets were named as P45L9, P45L12, P45L15, P48L9, P48L12, P48L15, P51L9, P51L12 and P51L15 (P-Protein, L-Lipid), respectively. Fish fed diets with the lowest protein and lipid combination (P45L9) had the lowest growth performance. Weight gains (WG) of fish fed the 4 diets P48L12, P48L15, P51L9, and P51L12 were not significantly different (P > 0.05), but significantly higher (P < 0.05) than those of fish fed the other diets. Fish fed diets P48L12 and P48L15 had significantly lower (P < 0.05) feed conversion ratios (FCR) than the rest of the treatments. Protein retentions (PR) among fish fed the diets P45L12, P45L15, P48L12, P48L15, P51L9, and P51L12 were similar and significantly higher (P < 0.05) than those of fish fed the remaining diets. Protein sparing effect was observed in the treatments when fish was fed diets containing 45% or 48% dietary protein levels with dietary lipid increased from 9% to 12%. Fish fed diets with 9% lipid tended to have lower viscerosomatic index (VSI), hepatosomatic index (HSI), and whole-body lipid. Increasing dietary protein level significantly increased (P < 0.05) liver moisture and lipid while dietary lipid level increased liver lipid. Intestinal lipase activity increased significantly (P < 0.05) with increasing dietary lipid and protein levels while intestinal α-amylase and protease activities were not significantly influenced (P > 0.05) by dietary treatments. Based on these results, the diet containing 48% protein with either 12% or 15% lipid is the optimal for supporting growth and feed utilization of juvenile northern snakehead under the current testing conditions.